DESCRIPTION OF CONGENITAL RUBELLA SYNDROME SURVEILLANCE SYSTEM BASED ON SYSTEM COMPONENTS AT PROF. DR. W. Z JOHANNES KUPANG REGIONAL HOSPITAL IN 2025 - Wahyuni, Maria Magdalena Dwi; Weraman, Pius; Makara, Reskita Putri Ananda; Udin, Putri Emilia; Chelino, Anthonius Elsabertho; Tameno, Chaterinne Aprilia; Jehani, Claudia Margareth (JURNAL WIDYA MEDIKA, 2025)
Congenital Rubella Syndrome (CRS) is a collection of symptoms that occur in infants due to rubella virus infection during pregnancy, which can cause heart defects, visual and hearing impairments, and developmental delays. This study aims to describe the implementation of CRS epidemiological surveillance at Prof. Dr. W. Z Johannes Kupang Regional General Hospital. The study was conducted through secondary data analysis and a review of CRS surveillance implementation documents from 2023 to 2025. It was found that 64 CRS cases had been recorded, consisting of 1 definite CRS case, 23 clinical cases, 4 suspects, and 17 discarded cases. Surveillance was carried out in a sentinel manner and supported by an electronic recording system integrated with the Health Office up to the central level. The implementing staff consisted of specialist doctors, public health workers, and midwives. The analysis showed that the strength of surveillance implementation lies in the existence of integrated guidelines and reporting systems. Still, obstacles were faced, such as the unavailability of eye examination equipment, responsible persons who did not comply with the guidelines, and non-routine health promotion. The primary priority issue was the lack of eye examination equipment, which resulted in delays in diagnosis and data collection. As a remedial measure, it is recommended that hospitals immediately procure such equipment and strengthen rubella health promotion. In conclusion, although CRS surveillance at regional hospitals has been well-implemented, optimization of diagnostic facilities and public education is still needed to support the comprehensive elimination of CRS.